2020
DOI: 10.1021/acs.iecr.0c02985
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Efficient Materials for NPK All-in-One Granular Fertilization

Abstract: Food security is one of the biggest challenges for the next few decades, especially with the accelerated population growth rates. Therefore, achieving a better nutrient use efficiency is crucial to enhance crop yields and productivity, which depend directly on how macronutrients are supplied. It is notably complex because fertilizers are often applied as granules instead of more soluble powdered forms. Here, we propose a new model for an allin-one NPK fertilizer production, which allows quickly adjustable comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…[12][13][14][15] For field application, however, fertilizers are usually managed as granules or pellets, which are easier for handling and storing. 16 Therefore, by controlling local acidity and particle size, struvite can provide P fertilization more efficiently and safely. Recently, our research group accomplished both of these criteria with the development of fertilizer composites based on a polysulfide matrix containing dispersed ground struvite.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] For field application, however, fertilizers are usually managed as granules or pellets, which are easier for handling and storing. 16 Therefore, by controlling local acidity and particle size, struvite can provide P fertilization more efficiently and safely. Recently, our research group accomplished both of these criteria with the development of fertilizer composites based on a polysulfide matrix containing dispersed ground struvite.…”
Section: Introductionmentioning
confidence: 99%
“…In a pot experiment with maize, Giroto et al (2020) found that NPK-thermoplastic starch composites of either TSP or Bayóvar rock achieved higher shoot biomass than when the P sources were directly mixed with the soil, i.e. not applied as composites 26 . Previous studies with struvite application reported various outcomes depending on the source of the recycled struvite and soil type, generally presenting an equal or even higher efficiency than water-soluble fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…Granule engineering may provide tools to improve crop fertilizer formulations and nutrient use efficiency, notably those methods related to nanotechnology. , Nanocomposite fertilizers, such as fertilizer granules that comprise nanoparticles or nanostructures able to modify their nutrient delivery behavior, could be designed to increase the solubility of low reactivity sources, , avoiding nutrient immobilization . Ideally, nanocomposite fertilizers can synchronize the nutrient release with the plant’s demand , in the case of soluble sources.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Nanocomposite fertilizers, such as fertilizer granules that comprise nano-particles or nanostructures able to modify their nutrient delivery behavior, could be designed to increase the solubility of low reactivity sources, 13,14 avoiding nutrient immobilization. 15 Ideally, nanocomposite fertilizers can synchronize the nutrient release with the plant's demand 13,16 in the case of soluble sources. However, solubilization depends on the dispersion degree of such particles, avoiding agglomeration.…”
Section: Introductionmentioning
confidence: 99%